2001
DOI: 10.1002/1522-2675(20010516)84:5<1197::aid-hlca1197>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Selenocysteine‐Mediated Native Chemical Ligation

Abstract: C-Terminal peptide thioesters are shown to react efficiently with peptide fragments containing an Nterminal selenocysteine to give selenoproteins. In analogy to the native chemical ligation of thioesters and peptides containing N-terminal cysteines, the selenol presumably attacks the thioester nucleophilically to give a selenoester intermediate that subsequently rearranges to give a native chemical bond. The utility of this procedure was demonstrated by the synthesis of a selenium-containing derivative of bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 31 publications
1
116
0
11
Order By: Relevance
“…The pMob group can be removed by using a cleavage cocktail of TFA, m-cresol, thioanisole, and trimethylsilyl trifluomethansulfonate (TMSOTf) [42]. Trimethylsilyl bromide has also been used [29]. …”
Section: Synthesis Of Selenocysteine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pMob group can be removed by using a cleavage cocktail of TFA, m-cresol, thioanisole, and trimethylsilyl trifluomethansulfonate (TMSOTf) [42]. Trimethylsilyl bromide has also been used [29]. …”
Section: Synthesis Of Selenocysteine Derivativesmentioning
confidence: 99%
“…In contrast to the genetic approach by Arner, my group and several others have used expressed protein ligation to construct proteins containing selenocysteine semisynthetically [28][29][30][31]. Prior to these efforts, Hilvert had used a total chemical approach to create the first artificial selenoenzyme by activating a serine residue in subtilisin with phenylmethanesulfonyl fluoride and then treating the activated ester with hydrogen selenide to complete the conversion to selenocysteine.…”
Section: Selenium and The Split Personality Of The Genetic Codementioning
confidence: 99%
“…Since an excess amount of Sec derivatives are necessary for high-yield synthesis of selenopeptides, the improved routes reported here will be valuable for promoting the research that utilizes various selenopeptides as selenoenzyme models 5 or for other purposes. [12][13][14][15][16] On the other hand, for the case of Fmoc-protected Sec derivatives, it was found that a similar route through an iodide intermediate 14 (and tosylate 12) and subsequent selenation with a selenolate nucleophile (RSe -) does not work well, resulting in a low yield and partial racemization taking place. However, the racemization problem can be overcome by repeated recrystallization, though the yield decreases.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Long selenopeptides that possess a couple of Sec residues along the chain have also been synthesized by application of selenocysteine-based native chemical ligation (Sec-NCL). [14][15][16] To synthesize selenopeptides in a flask, particular Sec derivatives have to be utilized. (Figure 1), which have Boc protection on the amino group and MBn or MPM protection on the selenium atom, are useful for Boc-based selenopeptide synthesis as the MBn and MPM groups in these targets can be deprotected under satisfactory conditions in the final step of selenopeptide synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ligation chemistries has been developed for this purpose (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Application of the chemical ligation principle (1) has led to practical chemical syntheses of a wide variety of different classes of proteins (16).…”
mentioning
confidence: 99%